AFIKSASI SEBAGAI UPAYA INTEGRASI ANTARA TEORI TASRIF Al-AF‘AL KLASIK DENGAN MORFOLOGI MODERN - Habibi Muhammad Lutfi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
Ideally, linguists are able to integrate between the modern morphology and the classical inflection (tas{ri>f) in analyzing the Modern Arabic morphological process, so as to create a new theory that does not merely require studying Western linguistics. From this anxiety, this paper offers to provide a theory of modern Arabic morphological analysis that starts from tracing its scientific foundation and continues with the study of Arabic morpheme processes in terms of classical and modern morphology. Resultantly, it is found lthat the classical verbs inflection based on derivation (isytiqa>q) can be integrated with the modern morphology, particularly in relation with the affixation process.